THE EFFECT OF FINANCIAL DISTRESS, LEVERAGE AND CAPITAL INTENSITY ON TAX AVOIDANCE WITH FIRM SIZE AS A MODERATING VARIABLE - Wibisono; Erlina; Abdillah Arif Nasution (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze and determine the effect of Financial Distress, Leverage, and Capital Intensity on Tax Avoidance with Firm Size as a moderating variable in Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2024. This research uses a quantitative research method. The population in this study consists of all property and real estate companies listed on the Indonesia Stock Exchange, totaling 92 companies. The sample in this study comprises 18 companies with 108 observations during the research period. The data used are secondary, obtained from published company financial statements. Data collection was conducted through a documentation study. The data analysis methods used include descriptive statistics, panel data regression analysis, classical assumption tests, coefficient of determination (R²), partial significance tests (t-tests), and Moderated Regression Analysis (MRA) using Eviews software. The results of this study indicate that Financial Distress has no significant effect on Tax Avoidance; Leverage has no significant effect on Tax Avoidance; and Capital Intensity has a positive and significant effect on Tax Avoidance. Firm size does not moderate the effect of financial distress on tax avoidance. However, firm size does not moderate the effect of leverage and capital intensity on tax avoidance.